Embodied metaphors and interpersonal synchrony in the digital age: the case of remote working - Magni, Giulia; Amadini Genovese, Luana; Riva, Giuseppe; Repetto, Claudia (Frontiers in Psychology, 2025)
This paper explores the impact of technology-mediated (TM) communication on interpersonal synchrony through the integrated lens of social neuroscience, embodied cognition, and Conceptual Metaphor Theory (CMT). It focuses particularly on the case of remote working, which exemplifies the challenges and adaptations required when social interactions shift from face-to-face (FTF) to digital environments. While FTF communication enables interpersonal synchrony through rich sensorimotor cues, such as gaze, posture, and gesture, TM communication often reduces or distorts these embodied signals. This disconnection undermines critical neurobiological processes like mirror neuron activation and impairs shared intentionality, emotional resonance, and trust. The paper highlights how embodied metaphors, especially CLOSENESS IS INTIMACY, are destabilized in digital contexts, making social engagement more cognitively demanding and less intuitive. Despite these limitations, humans show adaptability, developing compensatory behaviors and recalibrating expectations over time. However, remote working environments often lack the embodied coherence necessary to fully support collaborative creativity and social cohesion. The paper argues for the redesigning of digital platforms with immersive, multisensory interfaces, such as haptic feedback and spatialized audio, that better simulate the embodied dynamics of FTF interactions. It calls for future research employing hyperscanning and ecologically valid methods to understand how synchrony unfolds across digital modalities and how metaphorical coherence might be restored. Ultimately, by reengaging the body as a central substrate for cognition and communication, this work advocates for a more human-centered evolution of remote work technologies that sustains connection, trust, and collective performance.